The Impact of Digital Literacy-Based Assignments on Students’ Mastery of Islamic Education and Learning Habits: A Multivariate Regression Analysis - Tamama Hafizah; Kusen Kusen; Amrullah Amrullah; Muhammad Taufiqurrahman (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: The Impact of Digital Literacy-Based Assignments on Students’ Mastery of Islamic Education and Learning Habits: A Multivariate Regression AnalysisObjective: This study aims to analyze the simultaneous effects of digital literacy assignments on the mastery of Islamic Education material on the theme of tolerance and learning habits of eighth-grade students at SMPN 08 Lebong. Method: This study uses a quantitative approach with survey methods and multivariate regression analysis to test the relationship between digital literacy, mastery of material, and learning habits. Results: Digital literacy-based assignments significantly influence both variables, contributing 42.8% to mastery of the material and 13.2% to learning habits. Conclusion: Digital literacy effectively improves mastery of Islamic Education material, but its influence on learning habits still requires support from other holistic strategies. Contribution: This study suggests that digital assignments should emphasize the learning habit formation process and the reinforcement of Islamic character values. These findings contribute to developing technology-based curricula relevant to Islamic education in the digital age.INDONESIAN: Pengaruh Penugasan Melalui Literasi Digital terhadap Penguasaan Materi PAI Tema Toleransi dan Kebiasaan Belajar Siswa: Analisis Regresi MultivariatTujuan: Penelitian ini bertujuan untuk menganalisis pengaruh penugasan melalui literasi digital terhadap penguasaan materi Pendidikan Agama Islam (PAI) tema toleransi dan kebiasaan belajar siswa kelas VIII SMPN 08 Lebong secara simultan. Metode: Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei dan analisis regresi multivariat untuk menguji hubungan antara variabel literasi digital, penguasaan materi, dan kebiasaan belajar. Hasil: Penugasan berbasis literasi digital memberikan pengaruh signifikan terhadap kedua variabel, dengan kontribusi sebesar 42,8% terhadap penguasaan materi dan 13,2% terhadap kebiasaan belajar. Kesimpulan: Literasi digital efektif dalam meningkatkan penguasaan materi PAI, namun pengaruhnya terhadap kebiasaan belajar masih memerlukan dukungan strategi lain yang lebih holistik. Kontribusi: Penelitian ini menyarankan agar penugasan digital didesain dengan penekanan pada proses pembiasaan belajar dan penguatan nilai-nilai karakter Islami. Temuan ini memberikan kontribusi penting bagi pengembangan kurikulum berbasis teknologi yang relevan dengan pendidikan Islam di era digital.